Implementation of Fiscal Policy of the Islamic State of Saudi Arabia and the Arab Emirates - Suradi; Yadi Janwari; Sofyan Al-Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to analyze the economic policies of Saudi Arabia and the Arab Emirates in anticipating the effects of fiscal policy on their national economies. These policies include international economic policy, fiscal policy, and monetary policy. This research uses qualitative research methods through scientific observation by collecting non-numerical data, focusing on creating solutions and meaningfulness. The results of the research show that there are efforts by the Kingdom of Saudi Arabia in its international economic policy. On the other hand, monetary policy is needed to stabilize the economy by supporting solid fiscal policy when the global world is flooded with liquidity such as nominal interest rates that are close to or below zero, so that the impact of lowering interest rates can trigger an outflow of cash from the stock market. In this case, the Kingdom of Saudi Arabia was very quick and responsive in implementing the combination of these policies. Meanwhile, the United Arab Emirates government is taking strategic steps, including in tax policy. This country issues various regulations related to taxation in terms of collecting tax funds and using tax funds through the state budget.